Poland - Michener, James A. (Random House, 1983)
Poland's history from the thirteenth century to modern times overshadows a 1981 dispute between Janko Buk, the leader of a group of militant farmers, and Szymon Bukowski, the communist Minister of Agriculture
Keywords: Agriculture; Farming; General Anthropology; Contemporary Literature & Fiction; Poland -- Fiction